PENGARUH SENYAWA NITROGEN PADA DESULFURISASI MINYAK DIESEL DENGAN KATALIS NIMO/AL2O3 DAN COMO/AL2O3 - Murti, Sri Djangkung Sumbogo; Faizal, Muhammad (Jurnal Energi dan Lingkungan (Enerlink), 2007)
Inhibiting effect of nitrogen compounds in petroleum diesel (gas oil) on theperformance of the catalyst NiMo/Al2O3 and CoMo/Al2O3 uponhydrodesulfurization (HDS) has been investigated using an autoclave reactor.Operating conditions used was 340oC temperature and initial pressure 50 kg/cm2H2. Oil sample used was diesel oil and diesel oil-free nitrogen. Stages of thereaction between hydrogen replacement is intended to find out more about otherinhibiting effects derived from byproducts such as H2S and NH3. The entirecompound in diesel oil was analyzed by GC-AED before and afterhydrotreatment. Catalysts NiMo/Al2O3 and CoMo/Al2O3 showed different activityin HDS and the effect of nitrogen compounds. In principle, the HDS to type withhighly reactive sulfur / reactive will be more resistant to inhibiting properties ofnitrogen than sulfur compounds are hard to react (refractory). In contrast, forcatalysts showed como real effect of nitrogen compounds. One of refractorycompounds are 4,6-dibenzothiophene (4,6-DMDBT), can effectivelyhydrogenated by the removal of hydrogen compounds and renewal nitrogen onthe HDS. This result shows the synergistic effect due to dischargesimultaneously both types of block. Furthermore, in brief reactive nitrogencompounds in the HDS also discussed in this paper.Kata kunci: hydrodesulfurisasi, hambatan senyawa nitrogen, katalisNiMo/Al2O3, CoMo/Al2O3, GC-AED